2019
DOI: 10.4315/0362-028x.jfp-18-383
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Numbers of Listeria monocytogenes in Various Ready-to-Eat Foods over a 5-Year Period in Estonia

Abstract: The prevalence and numbers of Listeria monocytogenes in various categories of ready-to-eat (RTE) food products taken from retail outlets and food industries over a 5-year period are presented. A total of 30,016 RTE food samples were analyzed for L. monocytogenes prevalence, and 3.6% were found to be positive. The highest prevalence was found for RTE fish and fish products (11.6%), especially for lightly salted and cold-smoked fish products. The overall prevalence of L. monocytogenes in other food categories wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…It is important, however, to highlight that the sampling focused on a specific category of ready-to-eat foods: specialty meats. In contrast, Koskar et al [24] analysed the prevalence of L. monocytogenes in a total of 30.016 RTE foods, which shows very different results to those attained in our study. Indeed, 3.6% of the samples were found to be positive, and the highest prevalence of bacteria was found in RTE fish and fish products (11.6%).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…It is important, however, to highlight that the sampling focused on a specific category of ready-to-eat foods: specialty meats. In contrast, Koskar et al [24] analysed the prevalence of L. monocytogenes in a total of 30.016 RTE foods, which shows very different results to those attained in our study. Indeed, 3.6% of the samples were found to be positive, and the highest prevalence of bacteria was found in RTE fish and fish products (11.6%).…”
Section: Resultscontrasting
confidence: 99%
“…For this reason, the adoption and implementation of good hygiene practices by operators handling ingredients is of fundamental importance to minimise the risk of bacterial contamination [7]. Although it is not possible to directly compare data from other studies [24] due to the many variables that can influence the analysis, such as the geographical area and the observation period, it is interesting to note that the official data reported at a national level confirm our results [25]. Indeed, the Italian Ministry of Health, in its review of the assessment conducted in January 2021 of the risk of the consumer's exposure to L. monocytogenes [25], showed contamination rates for raw fish and seafood products of 0.6%, while cured meat products, such as cooked ham and cured ham (2%), were among the foods with the highest positive rates.…”
Section: Resultsmentioning
confidence: 99%
“…L. monocytogenes is a foodborne pathogen and products that do not undergo sufficient thermal treatment to eliminate the pathogen or that are consumed without any processing are considered to be high-risk foods. Outbreaks of listeriosis have been linked to the contamination of unpasteurized milk and milk products, soft cheeses, fish and seafood, ready-to-eat meat products with the growing importance of plant-based novel food vehicles [ 4 , 5 , 6 ]. Foods with L. monocytogenes may become contaminated before or during processing due to the occurrence and/or persistence of the pathogen in the animal farms and the food-processing environment [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we assessed 570 food samples in China from 2014 to 2016, 39 RTE foods and 5 pasteurized milk samples (7.7%) tested positive for L. monocytogenes, concurrent with contamination of L. monocytogenes in RTE foods reported in Beijing (Wang W. et al, 2015) but significantly greater than that of RTE foods in Estonia (Koskar et al, 2019) and Tokyo, Japan (Shimojima et al, 2016). However, Wang et al (2018) reported that 16.2% of samples were contaminated with L. monocytogenes in retail outlets selling RTE foods and restaurants serving mutton in Zigong, Sichuan Province.…”
Section: Discussionmentioning
confidence: 99%